2022
DOI: 10.1111/ane.13706
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in patients with Unverricht–Lundborg disease ( EPM1 )

Abstract: Progressive myoclonic epilepsy-1A (EPM1) (OMIM #254800), or myoclonic epilepsy of Unverricht and Lundborg, is a rare neurodegenerative disorder. Its most common manifestations are myoclonus, seizures, ataxia and cognitive decline. [1][2][3][4] The disorder is caused by cystatin B (CSTB) gene mutations and inherited recessively. 4 CSTB codes a small protein called Stefin B/cystatin B that functions as an intracellular thiol protease inhibitor. It has been isolated from human spleen and liver and shows biased ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…As far as the comorbidities and mortality rates of ULD are concerned, we know from a single-center longitudinal study in Finland that patients with ULD tend to suffer from previously unappreciated comorbidities, including external injuries (e.g., ankle fractures), diabetes, and depression [28]. This study complements another Finnish study of 135 patients with ULD that demonstrated comparable survival rates with age-matched controls up to the age of 40, after which patients with ULD had worsening survival rates [29].…”
Section: Diagnostic and Phenotypic Advancesmentioning
confidence: 99%
“…As far as the comorbidities and mortality rates of ULD are concerned, we know from a single-center longitudinal study in Finland that patients with ULD tend to suffer from previously unappreciated comorbidities, including external injuries (e.g., ankle fractures), diabetes, and depression [28]. This study complements another Finnish study of 135 patients with ULD that demonstrated comparable survival rates with age-matched controls up to the age of 40, after which patients with ULD had worsening survival rates [29].…”
Section: Diagnostic and Phenotypic Advancesmentioning
confidence: 99%
“…The mental status of the patients is alert, but depression and mild decline in intellectual performance are seen as the disease progresses. Many patients also show comorbidities, with the common categories being behavioral disorders, endocrine disease, external injuries and mental, metabolic and nutritional diseases [30].…”
Section: Clinical Picturementioning
confidence: 99%